Melatonin-Stimulated Triacylglycerol Breakdown and Energy Turnover under Salinity Stress Contributes to the Maintenance of Plasma Membrane H+–ATPase Activity and K+/Na+ Homeostasis in Sweet Potato - Yu, Yicheng; Wang, Aimin; Li, Xiang; Kou, Meng; Wang, Wenjun; Chen, Xianyang; Xu, Tao; Zhu, Mingku; Ma, Daifu; Li, Zongyun; Sun, Jian (Frontiers in Plant Science, 2018)
Melatonin (MT) is a multifunctional molecule in animals and plants and is involved in defense against salinity stress in various plant species. In this study, MT pretreatment was simultaneously applied to the roots and leaves of sweet potato seedlings (Ipomoea batatas (L.) Lam.), which is an important food and industry crop worldwide, followed by treatment of 150 mM NaCl. The roles of MT in mediating K+/Na+ homeostasis and lipid metabolism in salinized sweet potato were investigated. Exogenous MT enhanced the resistance to NaCl and improved K+/Na+ homeostasis in sweet potato seedlings as indicated by the low reduced K+ content in tissues and low accumulation of Na+ content in the shoot. Electrophysiological experiments revealed that exogenous MT significantly suppressed NaCl-induced K+ efflux in sweet potato roots and mesophyll tissues. Further experiments showed that MT enhanced the plasma membrane (PM) H+–ATPase activity and intracellular adenosine triphosphate (ATP) level in the roots and leaves of salinized sweet potato. Lipidomic profiling revealed that exogenous MT completely prevented salt-induced triacylglycerol (TAG) accumulation in the leaves. In addition, MT upregulated the expression of genes related to TAG breakdown, fatty acid (FA) β-oxidation, and energy turnover. Chemical inhibition of the β-oxidation pathway led to drastic accumulation of lipid droplets in the vegetative tissues of NaCl-stressed sweet potato and simultaneously disrupted the MT-stimulated energy state, PM H+–ATPase activity, and K+/Na+ homeostasis. Results revealed that exogenous MT stimulated TAG breakdown, FA β-oxidation, and energy turnover under salinity conditions, thereby contributing to the maintenance of PM H+–ATPase activity and K+/Na+ homeostasis in sweet potato.